XEN‐augmented Baerveldt surgical success rate and comparison with the Ahmed Valve. Issue 7 (18th March 2020) - Teixeira, Filipa Jorge; Sousa, David Cordeiro; Machado, Nuno Martins; Caiado, Filipa; Barão, Rafael; Sens, Paula; Abegão Pinto, Luís
Abstract: Purpose: The Baerveldt‐XEN technique is intended to reduce the risk of early hypotony after Baerveldt implant, while keeping a good long‐term intra‐ocular pressure (IOP) control. The aim of this study is to discuss the surgical success rate of the Baerveldt‐XEN and compare it with the commercially available flow‐restrictor device (Ahmed glaucoma valve – AGV). Methods: Single‐centre, cohort study. Consecutive glaucoma patients with uncontrolled IOP > 21 mmHg on maximum tolerated medical therapy, and who had an aqueous shunt as the planned surgical procedure. Patients underwent implantation of Baerveldt‐XEN. An age‐, gender‐ and glaucoma aetiology‐matched database of AGV patients was used for comparison. Complete surgical success was defined as a final IOP between 6 and 21 mmHg, and 20% reduction from baseline with no need for IOP‐lowering medication. Qualified success was the same criteria but resorting to medications. Results: Twenty‐four eyes from 24 subjects with glaucoma were included in this study, 12 patients underwent Baerveldt‐XEN implantation and 12 AGV. Twelve months after the Baerveldt‐XEN implant, the IOP reduced from 33 ± 9 mmHg to 14 ± 3 mmHg (p < 0.001). The qualified and complete success rate was 50% and 25%, respectively. With the AGV, the IOP reduced from 29 ± 7 mmHg to 16 ± 7 mmHg (p = 0.001). The matched AGV group compared to the Baerveldt‐XEN, presented a higher complete success rate (58.3%) and a qualified success rate of 33.3% (p = 0.72). No sight‐threatening complications were recorded in both groups. Conclusions: The Baerveldt‐XEN disclosed a low complete success rate at 1 year of follow‐up, although with no major safety concerns. While studies with a longer follow‐up are needed to demonstrate the potential advantages and disadvantages of the Baerveldt‐XEN, this technique may be less likely to achieve drop‐free efficacy when compared to other flow‐restrictor strategies.